2008
DOI: 10.1111/j.1478-3231.2008.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Budd–Chiari syndrome: illustrated review of current management

Abstract: Budd-Chiari syndrome (BCS) is characterized by hepatic venous outflow obstruction at any level from the small hepatic veins to the atriocaval junction. BCS is a complex disease with a wide spectrum of aetiologies and presentations. This article reviews the current literature with respect to presentation, management and prognosis of the disease. Medical, interventional and surgical management of BCS is discussed. Particular attention is paid to interventional and surgical aspects of management. The review is au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 56 publications
1
82
0
14
Order By: Relevance
“…Its aetiology has been associated with the presence of thrombophilia and myeloproliferative diseases. The rarity of the condition has not allowed for concise reports of its worldwide prevalence [129].…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Its aetiology has been associated with the presence of thrombophilia and myeloproliferative diseases. The rarity of the condition has not allowed for concise reports of its worldwide prevalence [129].…”
Section: Liver Diseasesmentioning
confidence: 99%
“…According to possible sites of obstruction, BCS may be divided into hepatic vein obstruction, inferior vena cava obstruction and a mixture of hepatic vein and inferior vena cava obstructions. Development of effective vascular surgery and interventional treatment approaches for the treatment of BCS associated with diffuse hepatic vein obstruction is difficult (3,4). Multiple studies have shown that portal vein-vena cava surgical shunt does not increase the survival of BCS patients (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The most common underlying disorders are myeloproliferative, such as polycythemia vera and essential thrombocytosis. 4,5 Other causes include factor V Leiden mutation, oral contraceptive use, protein C and S deficiencies, antiphospholipid syndrome, antithrombin III deficiency, paroxysmal nocturnal hemoglobinuria, cancer, Behçet syndrome, trauma, and idiopathic disorders. 4,6 Treatment options for BCS include anticoagulation, percutaneous interventional techniques, transjugular intrahepatic portosystemic shunt (TIPS), surgical shunts, and liver transplant.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Other causes include factor V Leiden mutation, oral contraceptive use, protein C and S deficiencies, antiphospholipid syndrome, antithrombin III deficiency, paroxysmal nocturnal hemoglobinuria, cancer, Behçet syndrome, trauma, and idiopathic disorders. 4,6 Treatment options for BCS include anticoagulation, percutaneous interventional techniques, transjugular intrahepatic portosystemic shunt (TIPS), surgical shunts, and liver transplant. 4 Therapeutic procedures are introduced in order of increasing invasiveness, based on the patient's response to previous therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation